Palladium‐Catalyzed Divergent Arylation with Triazolopyridines: One‐Pot Synthesis of 6‐Aryl‐2‐α‐styrylpyridines. Issue 6 (25th January 2016) - Moon, Youngtaek; Kwon, Soonhyung; Kang, Dahye; Im, Honggu; Hong, Sungwoo
Abstract: We have developed a new strategy for palladium‐catalyzed arylation reactions with triazolopyridines, wherein two different chemical transformations (C‐3 vs. C‐7) are observed by differentiating the substrates using different bases. The reactive palladium carbenoids were directly generated from triazolopyridines and underwent denitrogenative arylations with aryl bromides. Intriguingly, when potassium carbonate was replaced with potassium tert ‐butoxide, direct CH arylation occurred at the most acidic position (C‐7). Moreover, two different catalytic arylation events were successfully performed in a one‐pot sequence, providing a convenient access to 6‐aryl‐2‐α‐styrylpyridines. Abstract :